Determinan Keputusan Investasi Pada Cryptocurrency - Irvin Ng; Johny Budiman; Junita Junita; Viviani Viviani; Lindawati Lindawati; Joey Joey (Jurnal Bina Manajemen, 2023)
Cryptocurrency is becoming more and more popular as an investment asset. With a high risk high return characteristic of cryptocurrency, doesn’t stop people from investing into cryptocurrency. This research will study empirically regarding determinants behind cryptocurrency investment decisions with The Theory of Planned Behavior applied and added perceived risk as extra variable as well as the mediating role of attitude in behavioral intention to invest in cryptocurrencies. It is found that attitude, perceived behavioral control and subjective norm are key drivers behind cryptocurrency investment decision with perceived risk not affecting the behavioral intention. Attitude also mediates relationship between perceived behavioral control and subjective norm towards behavioral intention while attitude fails to mediate perceived risk towards behavioral intention to invest in cryptocurrency